Strength Through Unity: The Power of the Mega-Scaffold MACF1 - Cusseddu, Rebecca; Robert, Amélie; Côté, Jean-François (Frontiers in Cell and Developmental Biology, 2021)
The tight coordination of diverse cytoskeleton elements is required to support several dynamic cellular processes involved in development and tissue homeostasis. The spectraplakin-family of proteins are composed of multiple domains that provide versatility to connect different components of the cytoskeleton, including the actin microfilaments, microtubules and intermediates filaments. Spectraplakins act as orchestrators of precise cytoskeletal dynamic events. In this review, we focus on the prototypical spectraplakin MACF1, a protein scaffold of more than 700 kDa that coordinates the crosstalk between actin microfilaments and microtubules to support cell-cell connections, cell polarity, vesicular transport, proliferation and cell migration. We will review over two decades of research aimed at understanding the molecular, physiological and pathological roles of MACF1, with a focus on its roles in developmental and cancer. A deeper understanding of MACF1 is currently limited by technical challenges associated to the study of such a large protein and we discuss ideas to advance the field.